Environmental Issues-based Discovery Learning to Enhance Metacognitive Awareness and Students’ Higher-Order Thinking Skills - Wiono, Wisnu Juli; Meriza, Nadya (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2022)
This study aimed to describe students' metacognitive awareness and higher-order thinking skills through environmental issues-discovery. The research design was quasi-experimental with a pretest-posttest design. The data were collected through 52 Metacognitive Awareness Inventory (MAI) statements and the critical thinking test. The results show that the levels of students' metacognitive awareness are undeveloped (18 Percent), at-risk (8 Percent), poor (15 Percent), developed (22 Percent), high (14 Percent), and excellent (23 Percent). The discovery learning model significantly affects students' higher-order thinking skills (significant value of 0.000 with a 0.05 confidence level). Therefore, teachers are advised to utilize the surrounding environment in the discovery learning model to improve higher-order thinking skills and metacognitive awareness. Studies on other learning models need to be carried out to add references in organizing the learning process.